From Da‘wa to Politics? Prospects of Indonesian Salafi Movements Becoming Political Parties within Lucardie’s Framework - Afandi, Muhamad Ridwan; Ningsih, Sabda; Rizqullah, Muhammad Naufan; Erman, Ery; Prameswari, Ayu; Arifin, Jafar (Universitas Islam Indonesia, 2025)
This paper investigates the prospects of Indonesian Salafi movements transforming into formal political parties by applying Lucardie’s (2000) framework of political project, resource mobilization, and political opportunity structures. While Salafi political participation in contexts such as Egypt, Tunisia, and Malaysia has been widely studied, systematic application of this framework to Indonesia remains limited. This study addresses that gap by employing a qualitative design based on seven elite interviews conducted in 2018 and extensive secondary literature. The analysis identifies two main factions: Traditional Salafis and Salafi Reformers. Findings show that Traditional Salafis articulate a clearer political project, primarily defensive and oriented toward protecting da‘wa spaces, yet lack the institutional resources and cultural legitimacy required for effective party formation. By contrast, Reformist-oriented groups such as Muhammadiyah, Persis, and Al-Irsyad possess robust organizational infrastructures and nationwide networks but consistently reject transformation into political parties, preferring to channel influence indirectly through education, civic engagement, and individual cadres. A paradox therefore emerges: factions with stronger political ambitions lack the capacity to mobilize, while those with resources deliberately avoid party politics. Although digital platforms and hijrah youth networks have expanded Salafi symbolic capital, these remain insufficient to overcome entrenched barriers in Indonesia’s political culture, which is dominated by moderate Islam and stigmatizes Salafi labels. Theoretically, this study contributes by extending Lucardie’s framework through the inclusion of digital mobilization and cultural legitimacy as decisive factors. Practically, it suggests that inclusive democratic spaces for non-violent Islamist actors may mitigate radicalization risks while strengthening pluralism.